Helicons and magnetoimpurity waves in layered conductors
It is shown that local electron states, caused by impurities in a layered conductor placed in an external magnetic field, give rise to resonant corrections dsab(w) to the high-frequency conductivity tensor dsab(w) of the layers. These corrections appear due to the resonant transitions of electrons between the Landau levels and the local states and change dramatically the spectrum of collective electromagnetic oscillations in the system because of the &quotbranch crossing&quot nearby the frequency w0(hw0is the local state energy). As a result, a new magnetoimpurity wave,w_k, appears in the spectrum in addition to the helicon mode,w+k, which is known to exist in a pure layered conductor in a perpendicular magnetic field (k is the wave vector along the magnetic field). In the long wavelength limit, ka